Simulation of a Right Anterior Thoracotomy Access for Aortic Valve Replacement Using a 3D Printed Model. Issue 5 (September 2019) - Wamala, Isaac; Brüning, Jan; Dittmann, Johannes; Jerichow, Samuel; Weinhold, Joachim; Goubergritis, Leonid; Hennemuth, Anja; Falk, Volkmar; Kempfert, Jörg
Abstract : Objective: The right anterior lateral thoracotomy (RALT) approach for aortic valve replacement provides excellent outcomes in expert hands while avoiding sternal disruption. It, however, remains a technically demanding niche operation. Instrument trajectories via this access are influenced by patient anatomy, the intercostal space chosen, and surgical retraction maneuvers. Methods: To simulate the typical surgical maneuvers, on an anatomically accurate model, and to measure the instrument trajectories, we generated a 3-dimensional (3D) printed model of the heart and chest cavity. A simulated approach to the base of the right coronary sinus via the medial-second intercostal, the lateral-second intercostal, or third intercostal space was made. Keeping the instrument in place, 3D scans of the models and geometrical measurements of the instrument trajectories were performed. Results: The 3D scans of the 3D printed model showed a high fidelity when compared to the original computed tomographic scan image geometry (mean deviation of 1.26 ± 1.27mm). The instrument intrathoracic distance was 75 mm via the medial-second, 115 mm via the lateral-second, and 80 mm via the third intercostal space. The 3D angulation of the instrument to the incision was 33.77 o, 55.93 o, and 38.4 o respectively. The distance of the instrument to the lateral margin was 12, 26, and 5 mm respectively. The cranial margin of the incision was always a limiting margin for the instrument. Conclusions: Three-dimensional printing and 3D scanning facilitated a realistic simulation of the instrument trajectory during RALT approach. The lateral-second intercostal approach showed the most favorable approach angle and distance from the lateral margin, although it also had the longest intrathoracic distance.